Relationships between knowledge, attitude, and practices of food safety and hygiene among Muslim food truck handlers in the Klang Valley, Malaysia - Asha'ari, N. M. H.; Kamarulzaman, N. H. (Rynnye Lyan Resources, 2023)
Nowadays, the food truck business is gaining more popularity in Malaysia. It is a new trend for the new generation of street food lovers as a food service of ready-to-eat and fast food. Essentially, the fundamental aspects of halal food production include cleanliness, free from contamination, and healthy food. The processes include every aspect of personal hygiene, dress, equipment, and premise where food is processed and prepared. However, the outbreak of foodborne diseases is the consequence if there is an element of carelessness during the processing and handling of food, which is supposed to be in a more hygienic and safer environment. Unsanitary food handling procedures, poor water quality, and an unhygienic working environment were among the causes of foodborne illness cases in Malaysia. Therefore, the main objective of this study was to investigate the relationships between knowledge, attitude, and practices of food safety and hygiene among Muslim food truck handlers. Using convenience sampling, the data were collected from 121 Muslim food truck handlers in the Klang Valley in Peninsular Malaysia. A quantitative research survey was conducted using a structured, self-administered questionnaire to obtain responses from Muslim food truck handlers. Statistical analyses including descriptive analysis, Pearson correlation analysis, and Chi-square analysis were employed in this study. The findings showed that decent knowledge, attitude, and practices of food safety and hygiene among Muslim food truck handlers are crucial. These attributes have significant relationships, indicating that a better understanding of Muslim food truck handlers in terms of their knowledge, attitude, and practices of food safety and hygiene is critical to the long-term sustainability of the food truck business industry.